Navigating Gender Dynamics: Social Support and Psychological Distress in Elderly Individuals - Olorunjeedalo Anu Peters (Bisma The Journal of Counseling, 2023)
The ageing population in Nigeria, particularly in the region of Ile-Ife, Osun State, faces various challenges related to social support and psychological distress. The study on navigating gender dynamics, social support, and psychological distress in elderly individuals in Ile-Ife, Osun State, aims to examine the relationship between social support, gender dynamics, and psychological distress among the elderly population in a specific Nigerian community. The research delves into the impact of social support systems on the mental well-being of elderly individuals, particularly in the context of changing gender roles and dynamics within society. The sample consisted of 137 elderly persons from Ife Central Local Government using convenience sampling. The results showed that social support had no significant influence on psychological distress. It also revealed that sexual desire had a significant influence on psychological distress. The result further showed that gender had a significant influence on psychological distress. The study concluded that sexual desire and gender influenced psychological distress while social support did not.